Higher alkalinity increases copper toxicity in phytoplankton: The importance of pH flux when treating algal blooms - Anna C. Mollica; Megan T. Wesche; Matthew F. Gladfelter; Michael B. McDonald; Ashley V. Hennessey; Peyton P. Johnson; Kate L. Merrill; Alan E. Wilson (Harmful Algae, 2026)

Local and Landscape‐Level Environmental Conditions Drive Habitat Selection Across Terrestrial Mammal Species - Björn H. Franke; Aafke M. Schipper; Tal Avgar; Luca Börger; Nilanjan Chatterjee; Thomas Müller; Brian J. Smith; Briana Abrahms; Abdullahi H. Ali; Nina Attias; Hattie L. A. Bartlam‐Brooks; Floris M. van Beest; et al. (Global Ecology and Biogeography, 2026)
Aim Animal movements are a fundamental process affecting communities and ecosystems. Quantifying habitat selection across species and habitats is key for understanding how animals respond to environmental change. Currently, we lack comparative studies that examine how habitat selection varies across species traits and landscapes. We aim to quantify global patterns of habitat selection to help understand the fundamental drivers of movement behaviour. Location Global. Time Period Contemporary. Major Taxa Studied Terrestrial mammals. Methods We estimated selection coefficients for terrain ruggedness, vegetation productivity, human population density and distance to roads of individual terrestrial mammals through step‐selection analysis of 1344 GPS tracks across 48 species. We quantified intra‐ and interspecific variation and tested whether selection coefficients were associated with species traits and habitat availability. Results We observe an overall avoidance of roads and areas of high human population density as well as rugged terrain, with a large proportion of individuals selecting for areas of intermediate NDVI. However, we also found large intraspecific variation in habitat selection and show that this variation is predicted by local and landscape‐level environmental conditions rather than species traits. Individuals in more remote areas exhibited weaker functional responses to human presence than those in more disturbed areas. Avoidance of rugged terrain is also context‐dependent, with stronger avoidance when local ruggedness is high. The only exception to the observed intraspecific variability is consistent species‐level responses to road proximity. Main Conclusions Our findings contribute to the understanding of habitat selection by terrestrial mammals, showing that selection is largely shaped by environmental conditions and that animals exhibit high plasticity in their responses. Our results also provide further evidence for the significant impact of roads on animal movement. These insights can help us to understand the potential effects of environmental change on the behaviour of mammal species around the world.

Does Home and Wild Food Procurement Enhance Food Security in High-Income Countries? - Sam Bliss; Ashley C. McCarthy; Rebecca C. Mitchell; Scott C. Merrill; Rachel E. Schattman; Janica Anderzén; Meredith T. Niles (Current Environmental Health Reports, 2025)

Acceptability of a Fresh Produce Intervention for Individuals With Serious Mental Illnesses - Gabriella Farland; Leah G. Pope; En Fu; Dana Cohen; Cheryl Gerstler; Merrill Rotter; Michael T. Compton (Journal of Nutrition Education and Behavior, 2025)

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

Acute inorganic nitrate ingestion does not impact oral microbial composition, cognitive function, or high-intensity exercise performance in female team-sport athletes - Rachel Tan; Courtney Merrill; Chandler F. Riley; Maya A. Hammer; Ryan T. Kenney; Alyssa A. Riley; Jeffrey Li; Alexandra C. Zink; Sean T. Karl; Katherine M. Price; Luka K. Sharabidze; Samantha N. Rowland; et al. (European Journal of Applied Physiology, 2024)
The purpose of this study was to investigate the effects of acute nitrate (NO 3 − )-rich beetroot juice ingestion on explosive and high-intensity exercise performance, oral microbiota composition, and cognitive flexibility (i.e., function), before and after maximal intermittent running exercise. Fifteen women team-sport athletes were assigned in a randomized, double-blind, crossover design to consume concentrated NO 3 – -depleted beetroot juice (PL; 0.1 mmol NO 3 − ) and NO 3 − -rich beetroot juice (BR; 12.0 mmol NO 3 − ) 2.5 h prior to performing a battery of exercise performance tasks and cognitive testing before and after the Yo–Yo intermittent recovery level 1 (YYIR1) running test. Resting plasma [NO 3 − ] and plasma nitrite ([NO 2 − ]) were elevated following BR ( P < 0.001). BR did not impact global composition or relative abundance of taxa in the oral microbiome ( P > 0.05) or cognitive flexibility before or after exercise ( P > 0.05). There was no significant difference in performance during 20-m (PRE, PL: 4.38 ± 0.27 vs. BR: 4.38 ± 0.32 s; POST, PL: 4.45 ± 0.29 vs. BR: 4.43 ± 0.35 s) and 10-m sprints (PRE, PL 2.78 ± 0.15 vs. BR 2.79 ± 0.18 s; POST, PL: 2.82 ± 0.16 vs. BR: 2.81 ± 0.19 s), isokinetic handgrip dynamometry, medicine ball throw, horizontal countermovement jump, or YYIR1 (PL: 355 ± 163 m vs. BR: 368 ± 184 m) between BR and PL ( P > 0.05). These findings indicate that acute dietary NO 3 − may not influence the oral microbiome, explosive and high-intensity exercise performance, or cognitive function in women team-sport athletes.

Dust in the Critical Zone: North American case studies - J. Brahney; R.C. Heindel; T.E. Gill; G. Carling; J.M. González-Olalla; J. Hand; D.V. Mallia; J.S. Munroe; K. Perry; A.L. Putman; S.M. Skiles; B.R. Adams; et al. (Earth-Science Reviews, 2024)

A call to rename Ziphius cavirostris the goose‐beaked whale: promoting inclusivity and diversity in marine mammalogy by re‐examining common names - Ashley D. Rogers; Aileen Lavelle; Robin W. Baird; Arona Bender; Anna Borroni; Gustavo Cárdenas Hinojasa; William R. Cioffi; Brianna W. Elliott; Craig Harms; Anne E. Harshbarger; Ann‐Marie Jacoby; Kathryn Lienhard; et al. (Marine Mammal Science, 2024)

Into the danger zone: How the within‐host distribution of parasites controls virulence - Pieter T. J. Johnson; Tara Stewart Merrill; Dana M. Calhoun; Travis McDevitt‐Galles; Brendan Hobart (Ecology Letters, 2024)
Despite the importance of virulence in epidemiological theory, the relative contributions of host and parasite to virulence outcomes remain poorly understood. Here, we use reciprocal cross experiments to disentangle the influence of host and parasite on core virulence components—infection and pathology—and understand dramatic differences in parasite‐induced malformations in California amphibians. Surveys across 319 populations revealed that amphibians' malformation risk was 2.7× greater in low‐elevation ponds, even while controlling for trematode infection load. Factorial experiments revealed that parasites from low‐elevation sites induced higher per‐parasite pathology (reduced host survival and growth), whereas there were no effects of host source on resistance or tolerance. Parasite populations also exhibited marked differences in within‐host distribution: ~90% of low‐elevation cysts aggregated around the hind limbs, relative to

A pipeline for testing drug mechanism of action and combination therapies: From microarray data to simulations via Linear-In-Flux-Expressions - Christopher Denaro; Nathaniel J. Merrill; Sean T. McQuade; Logan Reed; Karim Azer; Benedetto Piccoli (Mathematical Biosciences, 2023)

Catchment-scale stream network spatio-temporal models, applied to the freshwater stages of a diadromous fish species, longfin eel (Anguilla dieffenbachii) - Anthony R. Charsley; Arnaud Grüss; James T. Thorson; Merrill B. Rudd; Shannan K. Crow; Bruno David; Erica K. Williams; Simon D. Hoyle (Fisheries Research, 2023)

The vitamin D receptor as a potential target for the toxic effects of per- and polyfluoroalkyl substances (PFASs): An in-silico study - Ettayapuram Ramaprasad Azhagiya Singam; Kathleen A. Durkin; Michele A. La Merrill; J. David Furlow; Jen-Chywan Wang; Martyn T. Smith (Environmental Research, 2023)

Improving estimates of the state of global fisheries depends on better data - Daniel Ovando; Ray Hilborn; Cole Monnahan; Merrill Rudd; Rishi Sharma; James T. Thorson; Yannick Rousseau; Yimin Ye (Fish and Fisheries, 2021)
Implementation of the United Nations Sustainable Development Goals requires assessments of the global state of fish populations. While we have reliable estimates of stock status for fish populations accounting for approximately half of recent global catch, our knowledge of the state of the majority of the world's “unassessed” fish stocks remains highly uncertain. Numerous publications have produced estimates of the global status of these unassessed fisheries, but limited quantity and quality of data along with methodological differences have produced counterintuitive and conflicting results. Here, we show that despite numerous efforts, our understanding of the status of global fish stocks remains incomplete, even when new sources of broadly available data are added. Estimates of fish populations based primarily on catch histories on average performed 25% better than a random guess. But, on average, these methods assigned fisheries to the wrong FAO status category 57% of the time. Within these broad summaries, the performance of models trained on our tested data sources varied widely across regions. Substantial improvements to estimates of the state of the world's exploited fish populations depend more on expanded collection of new information and efficient use of existing data than development of new modelling methods.

Cancer mortality risk, fine particulate air pollution, and smoking in a large, representative cohort of US adults - Nathan C. Coleman; Richard T. Burnett; Joshua D. Higbee; Jacob S. Lefler; Ray M. Merrill; Majid Ezzati; Julian D. Marshall; Sun-Young Kim; Matthew Bechle; Allen L. Robinson; C. Arden Pope (Cancer Causes & Control, 2020)

Dopamine receptor density and white mater integrity: 18F-fallypride positron emission tomography and diffusion tensor imaging study in healthy and schizophrenia subjects - Serge A. Mitelman; Monte S. Buchsbaum; Bradley T. Christian; Brian M. Merrill; Bradley R. Buchsbaum; Jogeshwar Mukherjee; Douglas S. Lehrer (Brain Imaging and Behavior, 2020)

Trade‐offs for data‐limited fisheries when using harvest strategies based on catch‐only models - Jessica C. Walsh; Cóilín Minto; Ernesto Jardim; Sean C. Anderson; Olaf P. Jensen; Jamie Afflerbach; Mark Dickey‐Collas; Kristin M. Kleisner; Catherine Longo; Giacomo Chato Osio; Elizabeth R. Selig; James T. Thorson; et al. (Fish and Fisheries, 2018)
Many of the world's fisheries are unassessed, with little information about population status or risk of overfishing. Unassessed fisheries are particularly predominant in developing countries and in small‐scale fisheries, where they are important for food security. Several catch‐only methods based on time series of fishery catch and commonly available life‐history traits have been developed to estimate stock status (defined as biomass relative to biomass at maximum sustainable yield: B/ B MSY ). While their stock status performance has been extensively studied, performance of catch‐only models as a management tool is unknown. We evaluated the extent to which a superensemble of three prominent catch‐only models can provide a reliable basis for fisheries management and how performance compares across management strategies that control catch or fishing effort. We used a management strategy evaluation framework to determine whether a superensemble of catch‐only models can reliably inform harvest control rules ( HCR s). Across five simulated fish life histories and two harvest‐dynamic types, catch‐only models and HCR combinations reduced the risk of overfishing and increased the proportion of stocks above B MSY compared to business as usual, though often resulted in poor yields. Precautionary HCR s based on fishing effort were robust and insensitive to error in catch‐only models, while catch‐based HCR s caused high probabilities of overfishing and more overfished populations. Catch‐only methods tended to overestimate B/ B MSY for our simulated data sets. The catch‐only superensemble combined with precautionary effort‐based HCR s could be part of a stepping stone approach for managing some data‐limited stocks while working towards more data‐moderate assessment methods.

A Resilience Framework for Chronic Exposures: Water Quality and Ecosystem Services in Coastal Social-Ecological Systems - Nathaniel H. Merrill; Kate K. Mulvaney; David M. Martin; Marnita M. Chintala; Walter Berry; Timothy R. Gleason; Stephen Balogh; Austin T. Humphries (Coastal Management, 2018)

Why do migrants move downhill? The effects of increasing predation and density on red deer altitudinal migration in temperate Carpathian forests - Peter Smolko; R. Kropil; T. Pataky; A. Veselovská; E. Merrill (Mammal Research, 2018)

A globally deployable strategy for co-development of adaptation preferences to sea-level rise: the public participation case of Santos, Brazil - Jose A. Marengo; Luci H. Nunes; Celia R. G. Souza; Joseph Harari; Frank Muller-Karger; Roberto Greco; Eduardo K. Hosokawa; Ernesto K. Tabuchi; Samuel B. Merrill; Catherine J. Reynolds; Mark Pelling; Lincoln M. Alves; et al. (Natural Hazards, 2017)

Rates of parasitism, but not allocation of egg resources, vary among and within hosts of a generalist avian brood parasite - Loren Merrill; Scott J. Chiavacci; Ryan T. Paitz; Thomas J. Benson (Oecologia, 2017)

Indirect effects of an invasive annual grass on seed fates of two native perennial grass species - Susan E. Meyer; Katherine T. Merrill; Phil S. Allen; Julie Beckstead; Anna S. Norte (Oecologia, 2014)

Pacific Atmospheric Sulfur Experiment (PASE): dynamics and chemistry of the south Pacific tropical trade wind regime - Alan Bandy; Ian C. Faloona; Byron W. Blomquist; Barry J. Huebert; Antony D. Clarke; Steven G. Howell; R. L. Mauldin; Christopher A. Cantrell; James G. Hudson; Brian G. Heikes; John T. Merrill; Yuhang Wang; et al. (Journal of Atmospheric Chemistry, 2011)

Spatial and non‐spatial risk factors associated with cage‐level distribution of infectious salmon anaemia at three Atlantic salmon, Salmo salar L., farms in Maine, USA - L Gustafson; S Ellis; T Robinson; F Marenghi; P Merrill; L Hawkins; C Giray; B Wagner (Journal of Fish Diseases, 2007)
The distribution of infectious salmon anaemia (ISA) was examined among 80 cages from three Atlantic salmon grow‐out farms in Maine, USA that were stocked with smolts from a single hatchery. Cage‐level disease was broadly defined as one or more moribund fish testing positive for infectious salmon anaemia virus (ISAV) by RT‐PCR and a second confirmatory test (IFAT, culture or genotype sequence). Spatio‐temporal and cage‐level risks were explored using logistic regression and survival analysis. Non‐spatial risk factors associated with ISA, or shortened survival time to disease, included increased predation, trucking company choice for smolt transfers, a finely‐sedimented benthic substrate, and smaller average size of smolts at stocking. Univariable analysis identified the time‐dependent spatial factor ‘adjacency to newly infected cages’ to be predictive of new infection in neighbouring cages 11–12 weeks later. However, none of the spatial factors, or their lags retained relevance in multiple‐variable models. The results suggest a diffuse distribution of virus exposure throughout infected sites, with host‐susceptibility factors probably influencing disease manifestation in individual cages. The narrow focus of the current study may limit application of the findings to other sites and year‐classes. However, these data support the relevance of husbandry efforts to optimize fish health in regions affected by ISAV.

Response to Host Volatiles by Native and Introduced Populations of Dendroctonus valens (Coleoptera: Curculionidae, Scolytinae) in North America and China - N. Erbilgin; S. R. Mori; J. H. Sun; J. D. Stein; D. R. Owen; L. D. Merrill; R. Campos Bolaños; K. F. Raffa; T. Méndez Montiel; D. L. Wood; N. E. Gillette (Journal of Chemical Ecology, 2006)

A novel method for patch-clamp automation - D. Vasilyev; T. Merrill; A. Iwanow; J. Dunlop; M. Bowlby (Pflügers Archiv - European Journal of Physiology, 2006)

Letters - T. La Farge; J. Merrill; G.L. Price; P. Buist; S. Pennington (Journal of Forestry, 2001)

Bulk rail shipments of potatoes from Washington - M. L. Weaver; T. A. Merrill (American Journal of Potato Research, 1965)